(untitled) (Journal of the College of Education for Women, 2021)
Persuasion is an indispensable skill in everyday life; that is why, it has aroused researchers’ interest. This study aims to investigate the most frequently used persuasive strategies in texting WHO COVID-19 Virtual Press Conferences and explore how these strategies are employed to achieve persuasive messages.To this end, a text of WHO COVID-19 Virtual Press Conferences has been chosen randomly to be analyzed based on Dillard and Shen’s (2013) “Persuasive strategies in Health Campaigns”. A qualitative method has been adopted in analyzing the selected data to investigate the credibility and validity of the persuasive strategies used in such a domain. Findings have shown that most of the persuasive appeals based on the adopted model are used, but in varying proportions. The total number of the persuasive strategies used in the data is (38) where the incentive appeals constitute 36% (14), the quantitative dissemination factors equal to 18 % (7), the one sided-vs. two-sided messages are 18 %(7), the evidence is 13 %(5), the message sources are 7 % (3), and the message qualities are 5 % (2), respectively. These frequencies show that ‘incentive appeals’ are mostly used. This is because Physical health, or factors, such as the economic, legal, psychological, social, and effort are the key dimensions of the incentive appeals. Each has a positive potential and negative evaluations based on audience’ predispositions. Accordingly, the field in which the persuasive appeals are used determines the frequent use of each one.